The Incidence of Fungal Infections in Patients Treated with Tocilizumab for Severe COVID-19 Pneumonia Requiring High Care or ICU Admission: A Retrospective Cohort Study - Naidu, Kuven; Richards, Guy A; Cruickshank, Deborah; Wadee, Bilaal; Naidu, Jayseelan; Kajee, Nabeela (European Journal of Applied Sciences, 2024)
Background: Critically ill COVID-19 patients often experience immune dysregulation, leading to cytokine release syndrome and an increased susceptibility to nosocomial infections, including invasive fungal infections. Early detection and treatment of fungal infections is paramount due to associated high mortality rates. Tocilizumab, an IL-6 receptor-blocking monoclonal antibody used in treating COVID-19 patients, has shown efficacy in managing the cytokine storm but is linked to a heightened risk of secondary fungal infections. Aims: This study aimed to investigate the association between Tocilizumab use and fungal infections in COVID-19 patients admitted to an ICU in South Africa. Methods: We conducted a retrospective cohort study at a private hospital in Johannesburg, South Africa, from April 2020 to August 2021. Data from 373 COVID-19 patients admitted to high care or ICU were analysed. Patients were categorized based on positive fungal cultures. Demographics, Tocilizumab usage, and relevant factors were collected from electronic databases. Results: Fungal infections were identified in 15.6% of the patients. Tocilizumab use did not significantly correlate with fungal infections (OR: 0.342 [95%CI: 0.115-1.019]; P=0.054). Factors associated with fungal infections included extended hospital stays (OR: 1.098 [95% CI: 1.038-1.163], P=0.050 and elevated D-dimer values (OR:1.20; [95% CI: 1.035-1.390]; P=0.015). Females were less likely to develop a fungal infection (OR:0.224; [95% CI: 0.054-0.928], P=0.039). Conclusions: Tocilizumab administration was not significantly linked to an increased risk of fungal infections in COVID-19 patients in the ICU. This study underscores the multifactorial nature of fungal infection risk, emphasizing the need for comprehensive risk assessment.